LMWH to prevent placenta‐mediated pregnancy complications: an update. (15th November 2014) - Duffett, Lisa; Rodger, Marc
Summary Placenta‐mediated pregnancy complications, including preeclampsia, placental abruption, intrauterine growth restriction/small for gestational age and recurrent or late pregnancy loss, affect over 5% of pregnancies and can result in significant maternal and perinatal morbidity and mortality. These complications have been suggested to at least partly arise from placental insufficiency, possibly as a result of inappropriate coagulation activation. This association has led to the hypothesis that anticoagulant therapy, such as low molecular weight heparin, might reduce their occurrence. The following review will attempt to summarize the extensive research that has been performed to date exploring this hypothesis and provide guidance on the current and future role of low molecular weight heparin in women at risk for placenta‐mediated pregnancy complications. A case will be made to question the widely adopted practice of prescribing low molecular weight heparin to women with prior placenta‐mediated pregnancy complications and suggest possible areas for future research.